Analysis and comparison of lipids in Saanen goat milk from different geographic regions in China based on UHPLC-QTOF-MS lipidomics. (July 2022) - Shang, Jiaqi; Liu, Ning; Cheng, Jianjun; Gao, Wenhao; Sun, Xiaomeng; Guo, Mingruo
Graphical abstract: Highlights: Lipids in Saanen goat milk from three regions in China were analyzed by lipidomics. A total of 638 lipids were identified and 173 lipids were significantly different. Thirteen potential lipid markers were screened out in goat milk from three regions. Significantly differential lipids were related with 71 metabolism pathways. Abstract: The lipids in goat milk from Guangdong Province (GGM), Shaanxi Province (SGM), and Inner Mongolia Province (NGM) were analyzed and compared using untargeted lipidomics. A total of 16 lipid sub-classes and 638 lipid molecules were identified in the three groups. The main lipids were diacylglycerol (DG), triacylglycerol (TG), and glycerophosphatidylethanolamine (PE). The contents of glycerophosphatidylcholine (PC), PE, glycerophosphatidylinositol (PI), sphingomyelin (SM), glucosylceramide (GlcCer), lactosylceramide (LacCer), DG, and TG were significantly different ( P < 0.05) in three groups. Moreover, 173 significantly different lipids were screened out, and 13 lipid molecules could be applied as potential lipid markers for identifying the geographic region of goat milk. In addition, the related metabolic pathways were also analyzed. A hypothetical scheme was drawn by linking the most relevant metabolic pathways. This work will provide basics for the establishment of the Saanen goat milk traceability system and provide comprehensive lipid information for the goat milk of different regions.